Penanaman Adab terhadap Al-Qur’an bagi Para Siswa di SD Plus Tahfizhul Quran Annida Salatiga - Devia Namira; Ahmad Fikri Sabiq (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2021)
[CULTIVATING ADAB TOWARDS THE QUR'AN FOR STUDENTS AT SD PLUS TAHFIZHUL QURAN ANNIDA SALATIGA] This study aims to determine the implementation of the cultivation of the Qur'anic adab which was carried out at PTQ Annida Elementary School Salatiga. This research is field research with a qualitative approach. Data collection techniques in this study were interviews, observation, and documentation. This study uses qualitative analysis, with a taxonomic analysis model. Adab is learning related to aspects of behavior and values, both in terms of individuals and society. There are many ways to instill etiquette in children, including the hiwar method, the uswatun hasanah method, the riyadhah method, the Ibrah method, and the story, the mau'idzah method, the targhib and tarhib methods as well as the Qur'anic and prophetic proverb methods. While some of the memorizations of the Qur'an that is instilled in children are to build a good relationship with the creator, avoid useless actions, build respect for the Qur'an as a holy book.